Joint resource configuration method for secure fog computing Internet of things - Shibo ZHANG; Hongyuan GAO; Yumeng SU; Jianhua CHENG; Lishuai ZHAO (Tongxin xuebao)
The current fog computing Internet of things (IoT) systems are prone to eavesdropping attacks in the process of physical communication transmission, and the existing research on fog computing has not effectively solved this problem.In order to realize the physical layer security (PLS) communication of the fog computing IoT to against the malicious eavesdropping of multiple eavesdroppers, a physical-layer secure fog computing Internet of things (PSFC-IoT) system was proposed.The secrecy rate of the proposed system in the secure communication scenario was analyzed, a joint resource management method based on the quantum bean optimization algorithm (QBOA) was proposed to solve the resource allocation problem of the network.The convergence performance of the proposed method was analyzed.Simulation results validate the efficiency of the proposed model and reveal the influence of various environmental parameters on system secrecy performance.In addition, the simulation results show that the proposed method can achieve the best secrecy performance for various communication scenarios.